A Non-Exploding Alkali Metal Drop on Water: From Blue Solvated Electrons to Bursting Molten Hydroxide; Angewandte Chemie International Edition; Vol. 55, iss. 42 - Mason P. E. Philip E.; Buttersack T. Tillmann; Bauerecker (Bauerekker) Z. (S.) H. Zigurd (Sigurd) Hermann; Jungwirth P. (2016, 2016)
Title screen